2017
DOI: 10.3390/ijerph14111420
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mortality in Patients with Isolated Traumatic Subarachnoid Hemorrhage Using a Decision Tree Classifier: A Retrospective Analysis Based on a Trauma Registry System

Abstract: Background: In contrast to patients with traumatic subarachnoid hemorrhage (tSAH) in the presence of other types of intracranial hemorrhage, the prognosis of patients with isolated tSAH is good. The incidence of mortality in these patients ranges from 0–2.5%. However, few data or predictive models are available for the identification of patients with a high mortality risk. In this study, we aimed to construct a model for mortality prediction using a decision tree (DT) algorithm, along with data obtained from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…This chapter is divided into 2 parts: data description and experimental results. To demonstrate completely the performance of WindNet proposed in this paper, this chapter will also include comparisons of very popular and commonly used machine learning algorithms, such as support vector machine (SVM) [33][34][35][36][37][38], random forest (RF) [39][40][41][42][43][44], decision tree (DT) [45][46][47][48][49][50] and MLP.…”
Section: Resultsmentioning
confidence: 99%
“…This chapter is divided into 2 parts: data description and experimental results. To demonstrate completely the performance of WindNet proposed in this paper, this chapter will also include comparisons of very popular and commonly used machine learning algorithms, such as support vector machine (SVM) [33][34][35][36][37][38], random forest (RF) [39][40][41][42][43][44], decision tree (DT) [45][46][47][48][49][50] and MLP.…”
Section: Resultsmentioning
confidence: 99%
“…The prediction accuracy of the DT models for survival on day 1 was 75.2% for Hostettler et al, 15 whereas Rau et al reported that DT achieved an accuracy of 97.9% for the prediction of death in patients with traumatic SAH. 21 NB, k-NN, and ANN are the algorithms used in ML for predicting classification. Hale et al studied the prediction of types of meningioma using several ML algorithms, reporting that ANN had the highest performance for predicting meningioma grade (AUC = 0.8895) compared with other algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…In order to fully demonstrate the performance of the EPNet proposed in this paper, this chapter includes comparisons between Support Vector Machine (SVM) [25][26][27][28][29][30], Random Forest (RF) [31][32][33][34][35][36], Decision Tree (DT) [37][38][39][40][41][42], MLP, CNN and LSTM. Figure 6 is the Electric Power Markets (PJM) Regulation Zone Preliminary Billing Data [43] used in this experiment, this data records the regulation market capacity clearing price of every half hour in 2017.…”
Section: Resultsmentioning
confidence: 99%